2018
DOI: 10.1016/j.bbmt.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Related Post-Transplantation Lymphoproliferative Disorders After Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Epstein-Barr virus (EBV)-related post-transplantation lymphoproliferative disorders (EBV-PTLDs) are rare but potentially fatal complications of allogeneic hematopoietic stem cell transplantation (allo-HSCT), characterized by uncontrolled proliferation of EBV-infected lymphocytes. The most common risk factors include T cell depletion of graft, HLA mismatch, severe graft-versus-host disease (GVHD), and EBV seromismatch (recipient-negative/donor-positive), among others. EBV-PTLDs commonly manifest as fever and ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…In the present study, we observed that at 6 months post-transplant during the immune reconstitution period, some patients are still unable to regulate the TTV replication, leading to high blood viral load, despite a sufficient number of T-cells. This observation has also been reported for other viruses such as cytomegalovirus (CMV) or Epstein–Barr virus (EBV) [ 9 , 27 , 28 ]…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, we observed that at 6 months post-transplant during the immune reconstitution period, some patients are still unable to regulate the TTV replication, leading to high blood viral load, despite a sufficient number of T-cells. This observation has also been reported for other viruses such as cytomegalovirus (CMV) or Epstein–Barr virus (EBV) [ 9 , 27 , 28 ]…”
Section: Discussionsupporting
confidence: 69%
“…The systemic immunosuppressive conditioning regimens plus ATG might delay immune reconstitution and thus increase the risk of infectious complications. Thus, EBV was associated with the post-transplantation lymphoproliferative disorder ( 28 , 29 ). Our pooled analysis showed that ATG increased subsequent EBV reactivation, while the incidence of general infection complications, CMV reactivation, and fungal infection did not change significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The use of VST cells for viral infections has a promising history, especially for the prevention or treatment of post-transplant opportunistic infections in the immunocompromised allogeneic bone marrow (allo-BM) recipients [2] , [51] , [52] , [53] , [54] , [55] , [56] . Many trials have shown that CMV-, EBV- and/or…”
Section: Virus-specific Effector Lymphoid Cellsmentioning
confidence: 99%
“…AdV-specific T cells were adequately immunoprophylactic to render the allo-BM transplanted patients viral-free for long-term. These VSTs were generated via 3 general strategies [2] , [51] , [53] , [54] , [55] , [56] , [57] : (1) coculture of seronegative donor-derived naïve T cells with the virus-specific Ag-loaded APCs ( Fig 3 c ), (2) activation and immunoadsorption of seropositive donor-derived PBMCs using viral protein-derived multimers or peptide pools and subsequent isolation of VST cells from the PBMCs using multimeter-based or IFN-γ capture-based immunomagnetic cell sorting ( Fig 3 d ), (3) genetic engineering of autologous T cells using gene vectors encoding the TCR specific to essential surface antigens of the virus ( Fig 3 e ). Additionally, there have been some efforts to engineer the CAR-bearing T cells for CMV and EBV that are effectual in an MHC-independent manner ( Fig 3 f ), though such CAR T cells merit further research and fine tunes in order to enter the clinical protocols [2] , [50] .…”
Section: Virus-specific Effector Lymphoid Cellsmentioning
confidence: 99%